Philadelphia - Saxon, Edward; Demme, Jonathan; TriStar Pictures; Clinica Estetico, Ltd; Columbia TriStar Home Video (Firm) (Culver City, California : Colombia TriStar Home Video, 2004)
Powerful story of two lawyers who join together to sue a prestigious Philadelphia law firm when the firm fires one of them because he has AIDS.
disc 1. The film ; filmmakers' Audio Commentary with director Jonathan Demme and screenwriter Ron Nyswaner - disc 2. special features ; people like us: making Philadelphia ; the critically acclaimed documentary One Foot on a Banana peel, the Ither Foot in the Grave ; deleted scenes ; includes the music video for the Academy Award ; courthouse protest footage and interviews ; Joe Miller's Macready & Shilts legal service TV spot ; original theatrical release featurette ; previews ; filmographies
Originally released as a motion picture in 1993
Editor, Craig McKay ; music, Howard Shore ; director of photography, Tak Fujimoto ; writer, Ron Nyswaner
Cast :Tom Hanks, Denzel Washington, Jason Robards, Mary Steenburgen, Antonio Banderas
Keywords: AIDS (Disease) -- Drama